Electronic properties and corrosion resistance of passive films on austenitic and duplex stainless steels. (20th May 2018) - Tranchida, G.; Clesi, M.; Di Franco, F.; Di Quarto, F.; Santamaria, M.
Abstract: Passive films were grown at constant potential in acidic (pH∼2) and alkaline (pH∼13) solutions on chromium, AISI 304L, AISI 316L and Duplex stainless steels. Passive films on chromium grow following a high field mechanism considering the presence of dissolution phenomena. According to the photoelectrochemical characterization, passive films on Cr have a bandgap of 3.4 eV when formed in acidic solution, and of 2.4 eV when formed in alkaline solution due to the formation of Cr(OH)3 . These films result to be poorly stable against anodic dissolution due to a very anodic flat band potential. Conversely, impedance and photoelectrochemical measurements proved that passive films on stainless steels are chromium rich oxide n-type semiconductors with a very high polarization resistance. Their band gap depends on the pH of the passivation solution and on the SS composition.